PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVC SDN 6 PEKANBARU - ', Norlina; ', erlisnawati; ', zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem this research is the student achievement of science lesson fourth graders SDN 6 Pekanabru still low with an average value of 68 and minimum completeness criteria (KKM) science lesson is 74. Between students, amounting to 35 students only 9 students who achieve classical KKM with 25,7%. This research is Classroom Action Research (CAR), which aims to improve the learning process in the classroom. Formulation of the problem: is the implementation of cooperative learning model type Numbered Heads Together (NHT) can improve students achievement of science lesson at SDN 6 Pekanbaru. The research was conducted on March 04, 2015 to 17 March, 2015by 2 cycles. The subject was students of SDN 6 , totaling 35 students who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained results cooperative NHT type of activity the teacher in the learning process in cycle I first meeting was 66,7% and at the second meeting of teacher activity increased by 12,5% to 70,8%. cycle II first meeting and the second meeting of activity increased by 12,5% to 91,7% and the second meeting of activity increased by 12,5% to 95,8%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an average of 66,7% and at second meeting of activity increased 8,3% to 62,5%% and a second meeting of activity increased 16,7% improve to 70,8%. At the first meeting of the second meeting of activity increased 12,5% to 95,8%. This research presents the results obtained each before the implementation an improve in base score cycles with the average being, 59,9. In the first cycle improve an average of 71,3 with increase as 28,57% and an improve in the second with an average of 91 with increase as 62,2%. Result in the research that the implementation of cooperative learning model of Numbered Heads Together (NHT) can improve student achievement of science lesson at fifth grader SDN 6 Pekanbaru.Key Words : Model Learning Think Pair Share (TPS), Fourth Grader Students Achievement2